2023
DOI: 10.1111/ene.15727
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the contribution of the gene TARDBP in Italian patients with amyotrophic lateral sclerosis

Abstract: Background and objectives Genetic variants in the gene TARDBP, encoding TDP‐43 protein, are associated with amyotrophic lateral sclerosis (ALS) in familial (fALS) and sporadic (sALS) cases. Objectives of this study were to assess the contribution of TARDBP in a large cohort of Italian ALS patients, to determine the TARDBP‐associated clinical features and to look for genotype–phenotype correlation and penetrance of the mutations. Methods A total of 1992 Italian ALS patients (193 fALS and 1799 sALS) were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Cognitive status was assessed in 24 patients: of these, 6 (25%) had cognitive involvement. These data are similar to those reported in a recent Italian study [34]. -c.881G>T, p.G294V: The number of familial cases (N = 13; 43.3%) was similar to that for sporadic cases (N = 17; 56.7%).…”
Section: Review Of Clinical Phenotypes Of Tardbp Mutations In Cases O...supporting
confidence: 90%
“…Cognitive status was assessed in 24 patients: of these, 6 (25%) had cognitive involvement. These data are similar to those reported in a recent Italian study [34]. -c.881G>T, p.G294V: The number of familial cases (N = 13; 43.3%) was similar to that for sporadic cases (N = 17; 56.7%).…”
Section: Review Of Clinical Phenotypes Of Tardbp Mutations In Cases O...supporting
confidence: 90%
“…Although previous studies have identified variants mostly in exon 6 [ 61 ], we found variants that span the whole coding sequence. Only one of the variants we found has been recorded before in ALS cases (c.995G>T p.G297V) [ 62 , 63 ]. This is the first study recording variants in UTR; specifically, we found two variants in 5′ UTR (c.5T>C; c.1347G>A) and two in 3′ UTR (c.1350A>G; c.24C>G).…”
Section: Discussionmentioning
confidence: 99%
“…Both of them have no or minimal influence on the protein, but they were found only in patients and not in healthy first-degree relatives. Moreover, the only variant we found that has previously been reported as associated with ALS and that both ClinVar and ClinGen classified it as both likely pathogenic and uncertain significance (c.995G>T p.G297V rs1643653768) [ 62 , 63 ] was also characterized as benign using the PolyPhen-2 tool; so, variants that do not significantly affect the amino acid sequence may have other consequences leading to pathogenesis, such as altering the gene’s expression. Another variant found only in patients and not in first-degree relatives is c.295G>A p.D64N, a missense variant characterized as possibly damaging by all in silico tools used.…”
Section: Discussionmentioning
confidence: 99%
“…There are no reports evaluating in depth cognitive and behavioral impairment of TARDBP-ALS, although the cognitive classification of TARDBP-ALS patients has been reported in some series. In cohorts of TARDBP-ALS patients of Italian ancestry, 5.5% to 30.3% of patients had various degrees of cognitive impairment, 22 - 24 but no detailed information related to impaired domains/tests was reported. Outside Italy, in a French cohort of 28 TARDBP-ALS, cognitive impairment was reported in two patients (7.1%), who carried the p.Gly295Ser and p.Gly384Arg variants, 25 whereas no one of the 4 TARDBP-ALS patients reported in a study from Switzerland had cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%